LITERASI PENGELOLAAN KEUANGAN PRIBADI BERBASIS PLATFORM DIGITAL BAGI GURU SMA SE-KOTA PONTIANAK DAN KABUPATEN KUBU RAYA - Erwin Febriansyah; Muliawati; Nasution, Hilfa Mora Marito; Gaol, Teddy Rianto L; Zultami, Sy Ilham; Lijanto, Callysta Angelica; Fadlila, Khaaiz Zulaal; Nazieh, Laazuardi; Winata, Valentino Chandra (IJTIMA’: JURNAL PENGABDIAN MASYARAKAT, 2026)
A digital platform-based personal financial management literacy activity is an effort to improve individuals' understanding and skills in managing finances effectively in the digital era. This activity was held on February 26, 2026, at Satu University, involving public and private high school teachers in Pontianak City and Kubu Raya Regency. Participants came from various schools, including Imanuel High School, Paulus High School, Bina Mulia High School, and State High School 04. The activity's implementation methods included material delivery, interactive discussions, and simulations of using digital platforms for personal financial management. The results showed an increase in participants' understanding of financial management, particularly in budget planning, financial recording, and the use of digital applications for financial monitoring. This activity had a positive impact on increasing teachers' awareness and skills as agents of financial literacy, which is expected to be transferred to students in the school environment.